1999
DOI: 10.1097/00006123-199902000-00026
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Long-term Intrathecal Morphine in the Management of Chronic Nonmalignant Pain

Abstract: Continuous intrathecal morphine can be a safe, effective therapy for the management of severe, nonmalignant pain among a carefully selected patient population and can result in long-term improvement in several areas of daily function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
154
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(167 citation statements)
references
References 35 publications
9
154
0
4
Order By: Relevance
“…However, the thirty-day mortality, which may not reflect the exact peri-operative mortality, is found to be at best 3.5% (3 out of 57) and at worst 10% (3 out of 30). The rate of serious complications (like bacterial meningitis, CSF leak and pump or catheter migration) from intrathecal analgesia is not clear in the literature but reports vary from 0% to 20% depending on the center, the population studied, and duration of follow up [14][15][16] . Anderson et al [16] and Kumar et al [14] reported a success rate of 50% and 75% respectively using intrathecal morphine in patients with chronic nonmalignant pain after an average duration of follow up of approximately 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the thirty-day mortality, which may not reflect the exact peri-operative mortality, is found to be at best 3.5% (3 out of 57) and at worst 10% (3 out of 30). The rate of serious complications (like bacterial meningitis, CSF leak and pump or catheter migration) from intrathecal analgesia is not clear in the literature but reports vary from 0% to 20% depending on the center, the population studied, and duration of follow up [14][15][16] . Anderson et al [16] and Kumar et al [14] reported a success rate of 50% and 75% respectively using intrathecal morphine in patients with chronic nonmalignant pain after an average duration of follow up of approximately 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Experience in this field, however, has been limited to case reports [10][11][12] . Among these, the intrathecal narcotic pump infusion (ITNP) is the most studied modality for control of intractable pain in cancer as well as non-cancer patients but with variable level of success [13][14][15][16] . The ITNP consists of a channeled catheter intrathecally (into the subarachnoidal space) that is connected to a small battery-powered programmable pump which is placed in the subcutaneous tissue of the abdominal wall.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the presence of such device, co-medication with one or combination of different classes of analgesics may still be necessary. A favourable result and a satisfactory pain control is then expected for approximately 60-95% of these patients [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Intraspinal infusion of opioid has been increasingly utilized since 1980s in patients with intractable, nonmalignant pain who have failed to respond to conventional treatment or could not tolerate systemic opioid therapy due to side effects [1][2][3][4][5][6]. By infusing small amount of opioid directly into cerebrospinal fluid in close proximity to the receptor sites in the spinal cord, one is able to achieve the spinally mediated analgesia sparing some of the side effects caused by systemic opioids.…”
Section: Discussionmentioning
confidence: 99%